Characterization of a new human plasma cell leukemia cell line UHKT-944 - Vyhlídalová, Ilona; Uherková, Lenka; Pleschnerová, Markéta; Špička, Ivan; Březinová, Jana; Michalová, Kyra; Čermáková, Kamila; Polanská, Veronika; Jedelský, Petr L; Hamšíková, Eva; Kuželová, Kateřina; Stöckbauer, Petr (European journal of haematology, 2015)
OBJECTIVE: A new interleukin-6 (IL-6)-dependent plasma cell leukemia cell line UHKT-944 was established from bone marrow cells derived from a 55-yr-old man with plasma cell leukemia. RESULTS: The cell line possesses phenotypic characteristics of plasma cells including the production of a monoclonal immunoglobulin IgA1-kappa. VH3-9 region of IgVH genes was rearranged and somatically hypermutated. The UHKT-944 cells were found to be negative for most of tested B-cell, T-cell, and myeloid markers. According to cytogenetic analysis, the cells were classified as near tetraploid with several numerical and structural abnormalities including the t(14;20) involving IgH locus. CONCLUSION: The established permanent plasma cell leukemia cell line is a suitable model for the study of cellular and molecular mechanisms of pathogenesis of this rare malignant disease.
Keywords: proliferace buněk; biologické markery; Cell Line, Tumor; Biomarkers; cytogenetické vyšetření; plazmocelulární leukemie; lidé; Cytogenetic Analysis; Immunoglobulins; Immunophenotyping; Leukemia, Plasma Cell; imunofenotypizace; Male; Cell Proliferation; lidé středního věku; imunoglobuliny; mužské pohlaví; Middle Aged; nádorové buněčné linie; Humans